The Relatıon Between Carıes Formatıon And Interdental Spaces In The Chıldren Aged Two And Four - Faik Çokpekin (Galenos Yayinevi, 1991)
In this study, it was investigated, interdental spaces during decidous dentition and their relation with caries formation on 550 children aged between two and four. As a result, the percentange of children was higher who has primate spaces than the children who has no primate spaces. But the number of children who has spaces at decidious incisors and decidious molars were lesser than the children who hasn't. It was observed, the incidence of caries formation was higher in the children has no spaces between teeth than the children has spaces.